WORSENING OF PSYCHOLOGICAL SYMPTOMS IN ALCOHOLICS COMPARED TO NONALCOHOLIC ANALYZED IN BRAZILIAN RESEARCH - Maria Aparecida da Silveira Brígido (European Scientific Journal, ESJ, 2014)
This article resulted from a research done on the psychological symptoms in alcoholic and non-alcoholic individuals and the analysis of differences between groups of alcoholics and nonalcoholic men and women. From the hypothesis whether there is difference in symptoms between alcoholic and nonalcoholic subjects some guided interviews were conducted for the application of the SCL 90-R instrument (Symptom Check List 90 - Revised) (Derogatis, 1983). This instrument intends to measure the intensity of symptoms, specifically in cases of alcoholism. The psychological symptoms evaluated were: Psychosis, Interpersonal Relationships, Anxiety, Paranoid Ideation, Hostility, Depression, Phobia and Obsessive Compulsive Disorder. The study population included not consuming alcohol persons in the community and alcoholic persons belonging to AA (Anonymous Alcoholics).It was found that, generally, there are differences between alcoholic and nonalcoholic subjects regarding to psychological symptoms, and that symptoms in alcoholics subjects are worsened.